Padre padrone l'educazione di un pastore - Ledda, Gavino 1938- (Feltrinelli, 1990)
Autobiography of Ledda, who spent his first twenty years as an illiterate shepherd living in Sardinia with his abusive father; he rebelled against both illiteracy and his father, and became a professor of linguistics.
Keywords: Ledda, Gavino <1938->; Geschichte 1960; Pastori - Italia - Sardegna - Biografia; Lehrer; Teachers -- Italy -- Sardinia -- Biography; Heranwachsender; Vater; Hirt; Junge; Zwang; Studium; Wissbegier; Italien; Sardinien; Biografie